Life History Aspects of the Hickory Shad (Alosa Mediocris) in the Albemarle Sound/ Roanoke River Watershed, North Carolina - Batsavage, Christopher F.; Rulifson, Roger (East Carolina University, 1998)
The hickory shad (Alosa mediocris), which supports commercial and recreational fisheries in the Roanoke River and Albemarle Sound, North Carolina, is an anadromous species closely related to the American shad (A. sapidissima). The Albemarle Sound population has exhibited a surge in numbers since 1989, but the cause is unexplained. Little is known about the life history of this species, which now supports a fast-growing sport fishery on the Roanoke River near Weldon, NC, and increased commercial catches in Albemarle Sound. The goal of this study was to characterize key life history aspects of hickory shad in the Albemarle Sound/Roanoke River watershed including the age, size, and sex compositions of the population, the sexual maturity schedule (age to maturity), potential fecundity of adults, and identification of the nursery grounds. Fish examined in this study were captured in 1996 from the Albemarle Sound and Roanoke River. The sex ratio(males:females) of adult fish sampled from Albemarle Sound and the Roanoke River at Weldon was statistically similar (0.73:1 and 0.76:1, respectively). A 57% agreement was found between aging fish with scales and otoliths; scales overestimated younger-aged fish and underestimated older-aged fish. Most males were age 3 and most females were age 4; few fish were older than age 4 and the maximum age was 7. Males were generally smaller than females; overlapping lengths and weights at age make estimates of size at age difficult. Some fish were mature by age 2, and all were essentially mature by age 3. Fecundity estimates ranged from 80,290 to 478,944 eggs with most fish spawning two or three times before leaving the population (from harvest or natural mortality). Reduced visceral fat of fish in the Roanoke River indicated use of stored lipid reserves during migration. Juvenile hickory shad apparently do not utilize Albemarle Sound as a nursery ground in the same manner as American shad and river herring (A. aestivalis and A. pseudoharengus), but they may use coastal ocean waters. A short life span and low fecundity makes this population vulnerable to overharvest.
Completion Report for Project M6057 to North Carolina Division of Marine Fisheries, Morehead City. ICMR Contribution series, NO. ICMR-98-02